1999
DOI: 10.1038/17618
|View full text |Cite
|
Sign up to set email alerts
|

The Rab5 effector EEA1 is a core component of endosome docking

Abstract: Intracellular membrane docking and fusion requires the interplay between soluble factors and SNAREs. The SNARE hypothesis postulates that pairing between a vesicular v-SNARE and a target membrane z-SNARE is the primary molecular interaction underlying the specificity of vesicle targeting as well as lipid bilayer fusion. This proposal is supported by recent studies using a minimal artificial system. However, several observations demonstrate that SNAREs function at multiple transport steps and can pair promiscuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
639
0
12

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 789 publications
(671 citation statements)
references
References 30 publications
20
639
0
12
Order By: Relevance
“…The simplest explanation for this difference in kinetics is that AMPA receptors that are internalized in response to insulin return more slowly to the surface. This hypothesis is consistent with our finding that AMPA receptors internalized in response to AMPA, but not in response to insulin, remain largely within a recycling endosome system, as defined by colocalization with EEA1, syntaxin 13 and TfR [32][33][34][35][36][37][38][39][40] . Unlike AMPA, insulin caused a divergence of internalized AMPA receptors out of the pathway delineated by EEA1, syntaxin 13 and TfR into a separate intracellular compartment.…”
Section: Ampa Receptor Endocytosis: Basal Regulated Recyclingsupporting
confidence: 92%
“…The simplest explanation for this difference in kinetics is that AMPA receptors that are internalized in response to insulin return more slowly to the surface. This hypothesis is consistent with our finding that AMPA receptors internalized in response to AMPA, but not in response to insulin, remain largely within a recycling endosome system, as defined by colocalization with EEA1, syntaxin 13 and TfR [32][33][34][35][36][37][38][39][40] . Unlike AMPA, insulin caused a divergence of internalized AMPA receptors out of the pathway delineated by EEA1, syntaxin 13 and TfR into a separate intracellular compartment.…”
Section: Ampa Receptor Endocytosis: Basal Regulated Recyclingsupporting
confidence: 92%
“…In another study carried out in the same cell type, we demonstrated that intracellular CD1a also colocalizes with Rab11 (Salamero et al, 2001), a small GTPase that specifically associates with the membrane of the endosomal recycling compartment (ERC) (Ullrich et al, 1996;Ren et al, 1998). Steady-state internal Langerin colocalized strongly with Rab11 in the ERC ( Figure 1E) but poorly with EEA1, a marker of the early/sorting endosomes ( Figure 1F) (Simonsen et al, 1998;Christoforidis et al, 1999;McBride et al, 1999 …”
Section: Langerin Is Associated With Rab11mentioning
confidence: 93%
“…In another study carried out in the same cell type, we demonstrated that intracellular CD1a also colocalizes with Rab11 (Salamero et al, 2001), a small GTPase that specifically associates with the membrane of the endosomal recycling compartment (ERC) (Ullrich et al, 1996;Ren et al, 1998). Steady-state internal Langerin colocalized strongly with Rab11 in the ERC ( Figure 1E) but poorly with EEA1, a marker of the early/sorting endosomes ( Figure 1F) (Simonsen et al, 1998;Christoforidis et al, 1999;McBride et al, 1999). The steady-state localization of Lange- rin was clearly different from that of CD1a, the latter being more equally distributed between the cell surface and internal membranes; however, this could be related to the dual role of the ERC as a sorting compartment for internalized proteins (Ghosh et al, 1998;Mallet and Maxfield, 1999;Wilcke et al, 2000) and as a storage reservoir for the regulated delivery of proteins to the plasma membrane (Johnson et al, 2001).…”
Section: Langerin Is Associated With Rab11mentioning
confidence: 93%
“…The Rab5 GTPase forms a domain by recruiting hVps34, causing localized production of PI3P (Christoforidis et al, 1999a). EEA1 stabilization on the GEECs also requires active Rab5 (Murray et al, 2002).…”
Section: Dominant-negative Rab5 Inhibits Fusion Between Geecs and Sormentioning
confidence: 99%